Istīrātīǧīyyāẗu āt-Tāʿlīmī āl-Luġāẗī āl-Aʿrābīyyāẗī āl-Aʿmāẗī līī āt-Tullābī āl-Mustāwā āl-Hāmīsī bīī āl-Ghāmīʿāẗī āl-Amien Prenduan - Hasanah, Uswatun; Hady, Alya Nafiesa; Kirom, Abdul; Masuwd, Mowafg (Mantiqu Tayr: Journal of Arabic Language, 2025)
This study aims to analyze the strategies used in teaching colloquial Arabic for tourism purposes to fifth-level students at University of Al-Amien Prenduan. The research responds to the growing need for tour guides capable of communicating in colloquial Arabic with tourists from the Middle East. Although Modern Standard Arabic is the main language of instruction at the university, the Arabic Language Education Department has included colloquial Arabic to meet labor market demands. The study adopts a qualitative descriptive method, with researchers acting as semi-participant observers through classroom observations, interviews with lecturers and students, and document analysis. The findings reveal, first: the teaching relies on two main strategies interactive teaching, which emphasizes student engagement and discussion for understanding, and the lecture strategy, where the instructor explains theoretical concepts and grammar rules related to colloquial Arabic. Second: there are supportive factors in the learning process, such as a friendly peer environment, the use of YouTube as a supplementary tool, and teacher competence. Third: several obstacles exist, including low student motivation, limited learning materials, and time constraints. The main conclusion is that successful colloquial Arabic instruction requires a balance between interaction and explanation, supported by an appropriate learning environment. The study recommends enhancing interactive strategies, using multimedia, and developing culturally appropriate materials for non-native speakers.